The Evolving Importance of Banks and Securities Markets - Demirguc-Kunt, Asli; Feyen, Erik; Levine, Ross (2012)
This paper examines the evolving importance of banks and securities markets during the process of economic development. As economies develop, they increase their demand for the services provided by securities markets relative to those provided by banks, such that securities markets become increasingly important for future economic development. Some exploratory evidence further suggests that deviations of a country s actual financial structure -- the mixture of banks and markets operating in an economy -- from the estimated optimal structure are associated with lower levels of economic activity.